PTH-018 Intravenous Ferric Carboxymaltose (ferinject) Given To Patients Post Endoscopy – Safe And Cost Effective. (9th June 2014) - Verma, AM; Das, D; Dixon, A; Chilton, AP
Abstract : Introduction: Intravenous (IV) iron is established as an effective management for patients with iron deficiency anaemia (IDA) and is indicated in those with severe iron deficiency, malabsorption, intolerance to oral iron and/or those requiring rapid correction of IDA. 1 The use of traditional agents iron dextran (CosmoFer) and iron sucrose (Venofer) are inexpensive in drug cost (£50–60), however they require test doses, slow intravenous infusions (4 h+) and the incidence of hypersensitivity reactions are high. This required a day case attendance which increased the overall cost of an infusion significantly. Then introduction of Ferric Carboxymaltose (FCM) has changed the landscape. Whilst the drug cost is 4 times higher, infusions only take 15 min and are much better tolerated. Also a higher dose of 1 g can be given. This only requires a short hospital appointment and reduces the overall cost of an infusion to less than traditional agents. The majority of patients with IDA undergo endoscopy for investigation +/- management. We trialled the use of IV FCM in patients whom it is indicated during the post-procedure observational time. Methods: Since January 2013, patients receiving IV FCM post endoscopy had their details recorded in a database. Results: - 15 patients underwent IV FCM infusion post endoscopy; - 9 women / 6 men, age range 33–83, mean age 64/ median 70; - Mean dose 940mg / median 935.7mg (12 patients received 1g IV); - 13 patients received IV sedation during endoscopy; - 6 had gastroscopy, 9 had colonoscopy; - Indication (s): Intolerant to oral iron 8, severe IDA 9 (GAVE, CRC), malabsorption 1; - Adverse events: 1 patient with bruising post IV cannula removal (not related to FCM). Conclusion: The safety and cost effectiveness of IV FCM has been established. This study shows that this is also the case for patients who receive IV FCM post endoscopy. The benefits of this approach are significant. Patients are already observed post-endoscopy so giving a short IV infusion is appropriate and does not require extra staff. This is also very convenient for patients, reducing the number of attendances required in addition to the benefits of IV iron for anaemia. Giving IV FCM post endoscopy reduces the costs significantly when compared those of a separate appointment to a day case unit. Reference: 1 Andrew F Goddard, Martin W James, Alistair S McIntyre, Brian B Scott, on behalf of the British Society of Gastroenterology. Guidelines for the Management of Iron Deficiency Anaemia. Gut 2011:60:1309–1316 Disclosure of Interest: None Declared.